Tailoring Biologic Therapies for Pediatric Severe Asthma: A Comprehensive Approach - Claudia María Chaverri Repáraz; Esther Lacalle Fabo; María Erroz Ferrer; María Gimeno-Castillo; Isabel Castro-Garrido; Miren Ibarzabal-Arregi; Nerea González Arza; Natividad Viguria; Laura Moreno-Galarraga (Children)
Introduction: Biologic therapies have revolutionized the management of severe asthma in pediatrics, offering targeted options for specific inflammatory pathways. This study aimed to review the current indications and availability of biologics approved for pediatric use as of January 2025 and to analyze the clinical experience of a tertiary center in managing this condition. Methods: A comprehensive review of the biologics available for treating severe asthma in children was conducted, highlighting their indications and key characteristics. Additionally, a retrospective analysis was conducted on the experience of the Pediatric Severe Asthma Unit at the University Hospital of Navarra in utilizing these therapies between 2015 and 2025, with a focus on treatment distribution and reasons for switching biologics. Results: As of January 2025, the biologics available for pediatric use include omalizumab, mepolizumab, dupilumab, tezepelumab, and benralizumab, each with specific indications and different administration profiles. At the analyzed center, the distribution of biologics was as follows: omalizumab (27%), mepolizumab (27%), dupilumab (37%), and tezepelumab (9%). At the same center, the biologic distribution 10 years earlier was 100% omalizumab. Therapy changes and switches were primarily related to clinical response, posology, and comorbidities. Conclusions: This study emphasizes the importance of individualized management in pediatric severe asthma, based on continuous evaluation and appropriate biologic selection according to the clinical characteristics of each patient. It also highlights the need to develop specific guidelines for adjusting, switching, and discontinuing these therapies.